Congenital Ocular Toxoplasmosis - Perry, Dwight D. (1983)
Congenital ocular toxoplasmosis is a significant cause of blindness. Retinochoroiditis is the most common finding, but other ocular manifestations include microphthalmus, nystagmus, strabismus, and ptosis. The serologic tests and lymphocyte stimulation test are the most useful aids in making the diagnosis. Pyrimethamine, sulfonamides, and corticosteroids are useful to treat active lesions. Primary care physicians, obstetricians, and ophthalmologists may help to prevent transmission of the disease and its serious ocular sequelae.